The potential for expanding inter-cluster cooperation between the ship-building industries of Estonia, Finland, and North-West Russia - Laaksonen Eini; Mäkinen Hanna (Baltic Region, 2013)
The shipbuilding industry clusters in the Eastern Baltic Sea region, i. e. Estonia, Finland and North-West Russia, may benefit significantly from increased mutual cooperation; however, the international networks between the clusters are still poorly developed. The aim of this article is to analyse the preconditions for cluster internationalization between these clusters, which are rather different but complementary in terms of skills. The research material for this desk study was collected from various sources, including journal articles, media, research reports, and other publications. The results of the study indicate that the increasing cooperation within the triangle of these clusters has a significant potential in terms of combining different areas of expertise and creating a multidimensional maritime industry hub in the region. However, differences in the cluster structure and development stages lead to certain difficulties in achieving these objectives. In conclusion, the authors identify the factors both facilitating and inhibiting networking between the three clusters. This study provides a platform for further research focusing on the factors identified and gives ideas for public discussion on increased inter-cluster cooperation.